Exogenous Phytase Added to Lipid Based Nutrient Supplements Increases Fractional and Total Absorption of Zinc Among Young Gambian Children: A Randomized Controlled Trial (OR07-01-19). (13th June 2019) - Wessells, K Ryan; Zyba, Sarah; Woodhouse, Leslie; Ceesay, Kabiru; Prentice, Andrew; Brown, Kenneth; Wegmuller, Rita
Abstract: Objectives: Dietary phytate inhibits zinc absorption from composite meals in adults. The objective of this study was to investigate the efficacy of adding exogenous phytase to a small-quantity lipid based nutrient supplement (SQ-LNS) on zinc absorption among young children. Methods: In a double-blind randomized controlled trial, intra-individual differences in fractional and total absorption of zinc (FAZ and TAZ, respectively) from SQ-LNS with and without phytase were measured in 30 asymptomatic 18–23 month old children in the Kiang West district of The Gambia. Using a cross-over design, children received for one day each test meals of a millet-based porridge with 20 g SQ-LNS containing 8 mg zinc and either: 1) exogenous phytase (∼500 phytase units (FTU)) or 2) no exogenous phytase. The test meals were provided on consecutive days in randomized order. FAZ was measured using a dual-stable isotope tracer ratio technique with 67 Zn and 70 Zn as oral tracers, randomized independently of SQ-LNS product, and 68 Zn as the intravenous tracer. TAZ was calculated as the product of total dietary zinc (TDZ) intake from test meals (i.e., porridge, SQ-LNS and stable isotope) and FAZ. FAZ and TAZ were compared for meals with and without phytase using mixed-models ANOVA with product, study day, and oral isotope allocation as fixed effects and individual child as a random effect. Results: Twenty-six participants completed the study. The prevalence of stunting, underweight and wasting were 20%, 30% and 13%, respectively; no children had low plasma zinc concentrations (< 65 μg/dL). TDZ and phytate intakes from the test meals were 7.2 ± 2.2 mg and 182.9 ± 64.7 mg, respectively (phytate: zinc molar ratio = 2.4 ± 0.2). Mean FAZ increased from 8.6 ± 1.3% to 16.0 ± 1.3% when exogenous phytase was added to the SQ-LNS product ( P  = 0.0002). Mean TAZ from porridge test meals containing SQ-LNS with phytase was more than double that from test meals containing SQ-LNS without phytase (1.12 ± 0.07 mg and 0.52 ± 0.07 mg, respectively; P  < 0.0001). Conclusions: The addition of exogenous phytase to a meal of millet-based porridge with SQ-LNS improved both FAZ and TAZ. These results suggest that phytate reduction may be an important strategy to improve zinc absorption among young children. Funding Sources: Nutriset, SAS.